Cytarabine delivered by CD44 and bone targeting redox-sensitive liposomes for treatment of acute myelogenous leukemia. (24th August 2022) - Wu, Hao; Gao, Yuan; Ma, Jia; Hu, Maosong; Xia, Jing; Bao, Shuting; Liu, Yuxi; Feng, Kai
Abstract: Acute myelogenous leukemia (AML) remains a serious fatal disease for the patients and effective treatment strategies are urgently needed. Based on the characteristics of the AML, we developed the CD44 and bone targeting liposomes delivery system decorated with the redox-cleavable polymer. First, ALN-HA was obtained by amination between alendronate (ALN) and hyaluronic acid (HA), and cholesterol (Chol) was coupled by a disulfide linker (-SS-) with biological reducibility to obtain the goal polymer, ALN-HA-SS-Chol, decorated the liposomes loaded with the Cytarabine (AraC). ALN-HA-SS-AraC-Lip exhibited a spherical morphology with the diameter of 117.5 nm and expanded at the environment of 10 mM dithiothreitol. Besides, compared with other groups, ALN-HA-SS-AraC-Lip showed benign hydroxyapatite affinity in vitro and bone targeting in C57/BL6 mice, also, ALN-HA-SS-AraC-Lip exhibited encouraging antitumor which significantly reduced the white blood cell amount in bone marrow and blood smear caused by AML model, besides, the dual targeting liposomes also prolong the survival time of mice. In conclusion, the bone and CD44 dual targeting liposomes with redox sensitivity could target to the leukemia stem cells regions and then uptake by the tumor cells, which would be a valuable target for the treatment of the AML. Graphical Abstract: